ANALISIS TALENT MANAGEMENT DAN KNOWLEDGEMANAGEMENT TERHADAP EMPLOYEE PERFORMANCE MELALUI EMPLOYEE RETENTION (Studi Pada Pegawai Direktorat Jenderal Pajak Kementerian Keuangan Republik Indonesia) - Maulana Hidayat (2020)
This research is a quantitative study that aims to determine the effect of Talent Management and Knowledge Management on Employee Performance through Employee Retention. The population in this study are Talent Ready Now employees at the Directorate General of Tax whose work location is in DKI Jakarta. The sample size was taken as many as 100 respondents, with non-probability sampling methods especially perposive sampling. Data collection was carried out through questionnaires. The analysis technique used is the PLS (Partial Least Square) analysis method. The results of this study indicate that (1) Talent Management has a significant and positive effect on Employee Performance with a path coefficient of 0.383 (2) Talent Management indirectly has no significant and negative effect on Employee Performance through Employee Retention with a path coefficient of 0.046 (3) Knowledge Management has a significant and positive effect on Employee Performance with a path coefficient of 0.297 and (4) Knowledge Management indirectly has a significant and positive effect on Employee Performance through Employee Retention with a path coefficient of 0.294